Factors Determining the Use and Cultivation of Moringa oleifera Lam. in the Republic of Benin. - Gandji, Kisito; SALAKO, Kolawolé Valère; FANDOHAN, ADANDE BELARMAIN; ASSOGBADJO, ACHILLE EPHREM; Glèlè Kakaï, Romain Lucas (My University, 2018)
Despite its nutritious leaves and considerable economic importance, the agroforestry species Moringa oleifera Lam. is still considered a neglected and underutilized species. To contribute to the development of an effective valorization strategy for M. oleifera, this study identified factors driving its use and cultivation in Benin. To this end, an ethnobotanical survey through individual interviews (n = 801) was performed in 46 localities across biogeographical zones in Benin. Conditional inference tree–based classification models allowed us to identify factors that mostly influence the use, cultivation, and cultivation system of M. oleifera. Awareness, knowledge of the plant biology, gender, cultivation system, and age are factors influencing the use of M. oleifera. Cultivation systems are driven by ethnicity, knowledge of the plant’s biology, and the main socioprofessional activity. Effective valorization of M. oleifera requires awareness rising on its usefulness while providing knowledge on the plant biology.
Keywords: Africa; agroforestry system; driving factors; Moringa oleifera L.; use